Distribution of anti-nuclear antibody pattern by immunofluorescence test at UKMMC in 2015 / Nur Farhani Husna Azizan - Azizan, Nur Farhani Husna (2015)
Antibody is a glycoprotein which mediates humoral immunity. Antibody- dependent cellular cytotoxicity is one of the ways how antibodies help to defend the body. In normal conditions, if an antigen is present on the patient red blood cells, the corresponding antibody will not be present in the patient plasma. However, when an antibody developed against its own self is happen, the patient then said to have an autoimmune disease. The antibodies that are created by the body against its own cell nuclei are called as anti-nuclear antibodies. The objective of this study is to recognize the common pattern of anti-nuclear antibody pattern using immunofluorescence test found at Universiti Kebangsaan Malaysia Medical Center. The data was classified into two types- general and specific data. Demographic data such as gender and age were also collected. The collected data then was described in numbers and percentages. All positive ANA IF tests from January 2015 to June 2015 was included while the duplicate ANA IF tests from the same patient between the study periods was excluded. The result shows 179 positive cases of ANA IF. Speckled was found as the most pattern of ANA IF with dominant 101 cases out of total 179 cases. Besides, Malay found as the most affected ethnic while adults age range between 36-59 years old were associated with positive ANA IF. Female gave an outstanding finding that dominate 86.03% of the research while the remaining 13.97% belongs to male.